“Antes era só ler, hoje em dia é ler e comentar”: leituras compartilhadas pela internet nos clubes Leia Mulheres - Rossi, Jean Silveira (2022)
The theme of this dissertation is limited to the study of shared reading practices and social uses of media by female readers who are members of the Leia Mulheres clubs, a Brazilian initiative that proposes the recognition of female writers through the collective reading of their works. The central question, entitled "How are cultural and communicational mutations configured in readings shared over the internet?", makes it possible to investigate shared reading practices in online meetings of Leia Mulheres clubs, based on narrative mediations, identities, technics, rituals and sociabilities, which is the general objective of the work. We take as specific objectives: a) to observe the shared reading practices in online meetings of five clubs belonging to the Leia Mulheres project in the country; b) understand the importance of the book club for the participating mediators and readers; c) analyze the uses of books and the internet by members of the Leia Mulheres project, based on the five mediations already mentioned. The qualitative research is based on cultural studies, especially on the theoretical-methodological approach of the mediations of Jesús Martín-Barbero (2018). Methodologically, we carried out an ethnographic study on the internet, organized in three moments. In 2020, we applied online questionnaires to 52 reading mediators who are part of the Leia Mulheres project. In the second stage, from March to August 2021, we carried out participant observation in three meetings of the Leia Mulheres de Marechal Deodoro (AL), Belém (PA), Mauá (SP), Sinop (MT) and Caxias do Sul (RS), totaling fifteen meetings. Finally, in November 2021 we interviewed five readers from these groups to deepen our analysis. As a result, we identified that the organization of Leia Mulheres goes through the mediations of technicalities, with regard to the use of the internet by clubs with production and sharing of content, in online meetings mediated by messaging applications, meeting platforms and social networks; rituals, through individual reading habits, choice of books, organization and repetition of meetings; sociability, through sharing readings, creating bonds and the impact of the pandemic on social relationships; narratives, in the face of personal and collective reports motivated by books as media products; and identities, based on the recognition of the self and the women authors, the feminist literary project and the club as a space for belonging and resistance.